Rediscovery of an extinct species of caviine rodent of the Late Pleistocene after the Last Glacial Maximum in the Pampasic Domain (Argentina) - Fernández, Fernando Julián (2025)
Galea tixiensis Quintana 2001, an extinct caviid species whose taxonomic status was questioned, has been identified at the Salto de Piedra (SPPL) paleontological site in Buenos Aires Province (Argentina). Morphological and morphometric analyses of these SPPL remains, together with contemporary and type locality specimens, support the taxonomic validity of this species. This identification dates the species back to ∼16,300 cal BP and extends its geographic distribution ∼200 km eastward in the Pampasic Domain. Other caviine include the extinct Microcavia cf. M. robusta. Paleoenvironmental correlations suggest that this diverse caviine fauna likely correspond to climatic and ecological shifts during the Pleistocene-Holocene transition. Species like M. robusta and Galea ortodonta disappeared as grasslands replaced shrub steppes in the region during the Holocene, and Cavia aperea arrived here from the north. Today, C. aperea is the only caviine species inhabiting the core of the Pampasic Domain, Microcavia australis and Galea leucoblephara remain restricted to southern xeric coastal environments and G. tixiensis appears to have become extinct in the 19th century. This study provides valuable insights into faunal shifts within the Pampasic Domain, linking these findings to broader patterns of Late Pleistocene biodiversity and environmental dynamics in South America.